2010
DOI: 10.4283/jmag.2010.15.1.021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Property of α-Fe2O3Nanoparticles Prepared by Sonochemistry and Take-off Technique

Abstract: A new synthetic method for the formation of uniform α-Fe 2 O 3 nanoparticles was reported and their magnetic properties were investigated. The sonochemical synthesis and the subsequent takeoff technique resulted in spherical shaped α-Fe 2 O 3 nanoparticles with an average diameter of 60 nm. The temperature-and applied magnetic field-dependent magnetization of the α-Fe 2 O 3 nanoparticles was explained by the sum of two contributions, i.e., the Morin transition and superparamagnetism, because the critical size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…[41] these grain diameters for these two samples were estimated, as 28.4 nm and 60.6 nm, respectively. Similar behavior to the BTF4 and BTF5 samples was reported in [53], where both the blocking process and the Morin phase transitions were observed for hematite nanoparticles with the diameter range 35 < d < 85 nm. It can therefore be concluded that, the BTF4 and BTF5 samples have wide grain diameter distributions, and even double distributions, where smaller nanoparticles exhibit the collective blocking process, while grains with the average size predicted in the above estimation undergo the Morin transition.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…[41] these grain diameters for these two samples were estimated, as 28.4 nm and 60.6 nm, respectively. Similar behavior to the BTF4 and BTF5 samples was reported in [53], where both the blocking process and the Morin phase transitions were observed for hematite nanoparticles with the diameter range 35 < d < 85 nm. It can therefore be concluded that, the BTF4 and BTF5 samples have wide grain diameter distributions, and even double distributions, where smaller nanoparticles exhibit the collective blocking process, while grains with the average size predicted in the above estimation undergo the Morin transition.…”
supporting
confidence: 84%
“…Also, the magnetic properties of hematite are not indifferent to the crystallinity of the samples, or the final shape and the surface structure of the grains [41][42][43][44][45][46][47][48][49][50]. Granular hematite systems, depending on the average dimensions of particles, d, may exhibit for T < T M only the Morin transition [51,42,52,[46][47], the Morin transition and the superparamagnetic (SPM) [46,53], or only the SPM state [38,[45][46][47][54][55][56]. It is well known, that the Morin transition is grain size dependent first-order phase transition described by the following equation predicted by Amin et all.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that none of the above transition temperatures is close to Morin transition in Fe 2 O 3 at 260 K (Ref. 32) and the Verwey transition in Fe 3 O 4 at 120 K, 33 eliminating the presence of iron oxides as impurity phases with any significant contribution to the magnetism of our samples.…”
mentioning
confidence: 92%
“…Many synthesis methods have been used to prepare Fe 2 O 3 nanoparticles [14][15][16][17][18]. A. Jahagirdar et al [2] synthesized dumbbell shaped α-Fe 2 O 3 nanoparticles by a low temperature combustion method and studied it's structural, magnetic and luminescence properties.…”
Section: Introductionmentioning
confidence: 99%